Respuestas

  • Usuario de Brainly
2013-05-01T04:39:08+02:00

 

tenemos nuestra identidad

 

\frac{tan(x)+cos(x)}{sen(x)}=sec(x)+cot(x)\\ \frac{tan(x)}{sen(x)}+\frac{cos(x)}{sen(x)}=sec(x)+cot(x)\\ \\ \frac{\frac{sen(x)}{cos(x)}}{sen(x)}+\frac{cos(x)}{sen(x)}=sec(x)+cot(x)\\ \\ \frac{1}{cos(x)}+\frac{cos(x)}{sen(x)}=sec(x)+cot(x)

 

sabemos que

 

\frac{1}{cos(x)}=sec(x)\\ \\ \frac{cos(x)}{sen(x)}=cot(x)

 

asi que 

\frac{1}{cos(x)}+\frac{cos(x)}{sen(x)}=sec(x)+cot(x)\\ \\ sec(x)+cot(x)=sec(x)+cot(x)